Resistance in cowpea cultivars to Bruchidius atrolineatus (PIC) (Coleoptera: Chrysomelidae: Bruchinae) - Boiça Júnior, Arlindo Leal; Copetti, Bárbara Marcasso; Rodrigues, Nara Elisa Lobato; Bottega, Daline Benites (Instituto Biológico, 2016)
ABSTRACT: This study aimed to assess the resistance in cowpea cultivars to Bruchidius atrolineatus (Pic) attack. The experiment was conducted at the Faculdade de Ciências Agrárias e Veterinárias of Universidade Estadual Paulista Júlio de Mesquita Filho (UNESP), Jaboticabal (SP). The following cultivars were used: BR17 Gurgueia, BR3 Tracuateua, BRS Novaera, Sempre Verde, BRS Milênio, and BRS Urubuquara. The non-preference test without choice evaluated the number of viable eggs, unviable and total posed by insects in grains, after 25 days of confinement. In addition, it was observed, in a daily basis, the total dry matter consumed and dry matter consumed per insect; male and female mass; male, female and total egg-adult cycle length; male and female longevity; sex ratio; number of emerged insects and percentage of emerged insects. The non-preference test with free choice evaluated the number of viable, unviable and total eggs and adult attractiveness after 24 hours and seven days of release. Sempre Verde cultivar was the least preferred for oviposition in the test without choice and showed lower number and percentage of emerged insects. BRS Milênio had the lowest total dry mass consumed and dry mass consumed per insect.

RESUMO: O objetivo do presente trabalho foi avaliar a resistência em cultivares de feijão-caupi ao ataque de Bruchidius atrolineatus (Pic). O experimento foi conduzido na Faculdade de Ciências Agrárias da Universidade Estadual Paulista Júlio de Mesquita Filho (UNESP), campus de Jaboticabal/SP. Seis cultivares foram utilizados: BR17 Gurgueia, BR3 Tracuateua, BRS Novaera, Sempre Verde, BRS Milênio e BRS Urubuquara. No teste de não preferência sem chance de escolha, foram feitas as avaliações do número de ovos viáveis, inviáveis e totais colocados pelos insetos nos grãos, após 25 dias de confinamento. Nas amostras foram observadas também, diariamente, a massa seca consumida e a massa seca consumida por inseto; a massa de machos e fêmeas; o período de ovo adulto de fêmeas, machos e total; a longevidade de machos e fêmeas; a razão sexual; e a porcentagem de insetos emergidos. No teste com chance de escolha foram realizadas as contagens de ovos viáveis, inviáveis e totais e avaliada a atratividade dos adultos após 24 horas e sete dias da liberação. O cultivar Sempre Verde foi o menos preferido para oviposição, em teste sem chance de escolha, e apresentou menor número e porcentagem de insetos emergidos. Já BRS Milênio teve a menor massa seca consumida total e por inseto.
Resistência em cultivares de feijão-caupi a Bruchidius atrolineatus (Pic) (Coleoptera: Chrysomelidae: Bruchinae)
Keywords: Vigna unguiculata; grains; grain weevil; Vigna unguiculata; grãos; caruncho